Optimalisasi Kesehatan dan Pendidikan untuk Pencegahan Penyakit Demam Berdarah Dengue Pada Masyarakat Kapurancak - Fahriza, Muhammad Risqi; Falah, Alfian Rudhi; Kurniawan, Muhammad Wahyu; Aeni, Diyan Nur; Aisah, Nur; Shidqi, Rifqi Abrar; Fatima, Dea Delfinda; Arfiansyah, Rifky Panji; Amanta, Amanta; Laksita, Putri; Kartika, Wisnu (Universitas Muhammadiyah Yogyakarta, 2025)
The Community Service Program implemented in Kapurancak Hamlet, Kopen Village, Teras Subdistrict, Boyolali Regency, focuses on efforts to prevent and control Dengue Fever (DHF) with the main objective of increasing public awareness and active participation in maintaining environmental hygiene. The main problem faced in this area is the high number of DHF cases caused by a lack of public awareness of the importance of maintaining environmental hygiene, as well as a lack of understanding of how to prevent the breeding of the Aedes aegypti mosquito, the main vector of DHF spread. The methods used in this program include direct observation in the field, interviews with local communities to find out their views, and documentation of activities. This program also applies facilitation techniques such as Focus Group Discussion (FGD), socialization, and direct assistance in the implementation of the 3M Plus movement (Draining, Covering, and Recycling) as well as education on the importance of maintaining environmental hygiene. One of the main programs implemented was the socialization of dengue fever, including how to prevent, treat, and the early symptoms of the disease. The results of the program showed a high level of community participation in this activity, as well as an increase in their understanding of the importance of maintaining environmental hygiene and preventing DHF. The socialization, which involved expert speakers, contributed to providing practical insights on how to prevent the breeding of Aedes aegypti mosquitoes. As a follow-up, the community service group provided mosquito larvae repellent (abate) to the community during the socialization as part of efforts to prevent the spread of DHF. The conclusion from this activity is that the community service program succeeded in raising community awareness about dengue prevention and control.